2020
DOI: 10.1007/s40258-019-00546-8
|View full text |Cite
|
Sign up to set email alerts
|

Health State Values of Deaf British Sign Language (BSL) Users in the UK: An Application of the BSL Version of the EQ-5D-5L

Abstract: BackgroundDeaf people experience health inequalities compared to hearing populations. The EQ-5D, a widely used, standardised, generic measure of health status which is available in over 100 languages, was recently translated into British Sign Language (BSL) and initial validation conducted. Using data from this previous study of the EQ-5D-5L BSL we aimed to assess (i) whether responses to the EQ-5D differed between a sample of Deaf BSL users and the general population (ii) whether socio-demographic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Health status was found to be poorer in the Deaf population compared with the general population in the self-report studies by Rogers et al [29] (EQ-5D mean index values 0.78 vs 0.84), and Shields et al [10] (43% vs 17% for depression symptoms). However, Kushalnagar et al [20], found that hearing people had worse overall health status compared with Deaf people, suggesting that age may be a contributing factor, as the mean age of the hearing sample was significantly older than that of the Deaf adults.…”
Section: Resultsmentioning
confidence: 99%
“…Health status was found to be poorer in the Deaf population compared with the general population in the self-report studies by Rogers et al [29] (EQ-5D mean index values 0.78 vs 0.84), and Shields et al [10] (43% vs 17% for depression symptoms). However, Kushalnagar et al [20], found that hearing people had worse overall health status compared with Deaf people, suggesting that age may be a contributing factor, as the mean age of the hearing sample was significantly older than that of the Deaf adults.…”
Section: Resultsmentioning
confidence: 99%
“…Using validated assessments in sign language, health status was found to be poorer in the Deaf population compared with the general population in the self-report studies by Rogers et al [ 29 ] (EQ-5D mean index values 0.78 vs 0.84), and Shields et al [ 10 ] (43% vs 17% for depression symptoms). However, Kushalnagar et al [ 20 ], found that hearing people had worse overall health status compared with Deaf people, suggesting that age may be a contributing factor, as the mean age of the hearing sample was significantly older than that of the Deaf adults.…”
Section: Resultsmentioning
confidence: 99%
“…Using the sign language version of the assessment and when the validation has been examined, Munro et al [ 41 ] reported that a clinical sample had a significantly lower mean score for wellbeing (18.57; SD = 9.6) compared with a non-clinical sample (27.04, SD = 8.68) on the ORS-Auslan. Overall health status was found to be poorer for Deaf people with depression compared to those with no psychological distress or depression [ 10 ]. Rogers et al [ 42 ] and Belk et al [ 43 ] found that severity of depression and anxiety was worse for those who self-reported as having mental health difficulties compared to those who did not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation